Semiotics of Photography in Print Advertisement - Ahmad Zakiy Ramadhan (IC-ITECHS, 2020)
Semiotics is a theory for analyzing works of art. One of the works of art that is interesting to be analyzed is print advertisements. Print advertisements convey messages to the target audience through symbols that have meaning. This meaning must be able to be interpreted appropriately by the target audience so that the information conveyed is right on target. One of the media tools for presenting symbols is photography. Usually ads have a persuasive message to influence the target audience to something. The most important thing in making an ad is choosing the appropriate symbols that will be interpreted by the creative team. The stages in this analysis are reading the displayed symbols and analyzing them with semiotic theory. The results of this analysis are in the form of interpretations of several advertising works that use photography techniques, with semiotic theory as the basis for the analysis.